L’approche énergétique de la rupture élastoplastique appliquée à la modélisation de propagation d’une entaille - Lorentz, Eric; Wadier, Yves (European Journal of Computational Mechanics, 2004)
An energy release rate is defined for a crack represented by a notch, relying on the theory of Francfort and Marigo and Continuum Damage Mechanics. Progressive as well as sudden crack propagation can be predicted. The paradox of Rice and the spurious scale effects of Francfort and Marigo’s theory induced by Griffith’s hypothesis can be eliminated. The results obtained in the case of the analysis of the « warm pre-stress effect » are in good agreement with the experimental results.